2003
DOI: 10.1016/j.curtheres.2003.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of policosanol on borderline to mildly elevated serum total cholesterol levels: a prospective, double-blind, placebo-controlled, parallel-group, comparative study

Abstract: Background: Hypercholesterolemia is a major risk factor for coronary heart disease. Clinical studies have shown that lowering elevated serum cholesterol levels, particularly low-density lipoprotein cholesterol (LDL-C), is beneficial for patients with borderline to mildly elevated serum total cholesterol (TC) levels (5.0-6.0 mmol/L). Policosanol is a cholesterol-lowering drug made from purified sugar cane wax. The therapeutic range of policosanol is 5 to 20 mg/d.Objective: This study investigated the efficacy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…One of the most extensively studied RYR nutraceutical combinations (Armolipid Plus ® ) includes berberine, a plant alkaloid that enhances the hepatic uptake of cholesterol, for which the largest pharmacovigilance datasets are available [ 75 , 76 , 77 ]. Armolipid Plus ® contains 3 mg monacolin K, 500 mg berberine, and 10 mg policosanols (aliphatic alcohols derived from sugar cane, reported to have cholesterol-lowering effects [ 78 ]). A meta-analysis of 12 randomized control trials involving 1050 subjects with up to 12 months’ follow-up showed that this preparation significantly decreased body-mass index (MD −0.25 kg/m 2 ; p = 0.008), LDL-C (MD −26.67 mg/dL; p < 0.001), TC (MD −25.07 mg/dL; p < 0.001), triglycerides (MD −11.47 mg/dL; p < 0.001), fasting glucose (MD −3.52 mg/dL; p < 0.001), and hs-CRP versus placebo (−0.61 mg/L; p = 0.022), and significantly increased HDL-C (MD 1.84 mg/dL; p < 0.001) versus placebo [ 76 ].…”
Section: Effect Of Ryr On Ldl-c Plasma Level and Estimated Risk Of Ascvdmentioning
confidence: 99%
“…One of the most extensively studied RYR nutraceutical combinations (Armolipid Plus ® ) includes berberine, a plant alkaloid that enhances the hepatic uptake of cholesterol, for which the largest pharmacovigilance datasets are available [ 75 , 76 , 77 ]. Armolipid Plus ® contains 3 mg monacolin K, 500 mg berberine, and 10 mg policosanols (aliphatic alcohols derived from sugar cane, reported to have cholesterol-lowering effects [ 78 ]). A meta-analysis of 12 randomized control trials involving 1050 subjects with up to 12 months’ follow-up showed that this preparation significantly decreased body-mass index (MD −0.25 kg/m 2 ; p = 0.008), LDL-C (MD −26.67 mg/dL; p < 0.001), TC (MD −25.07 mg/dL; p < 0.001), triglycerides (MD −11.47 mg/dL; p < 0.001), fasting glucose (MD −3.52 mg/dL; p < 0.001), and hs-CRP versus placebo (−0.61 mg/L; p = 0.022), and significantly increased HDL-C (MD 1.84 mg/dL; p < 0.001) versus placebo [ 76 ].…”
Section: Effect Of Ryr On Ldl-c Plasma Level and Estimated Risk Of Ascvdmentioning
confidence: 99%
“…Based on an expected LDL-C-lowering effect of at least 20 % (Castano et al 2002b(Castano et al , 2003c, this number of subjects would have provided at least 80 % power at a 5 % level of significance. The subjects signed informed consent forms for participation in the study.…”
Section: Subjectsmentioning
confidence: 99%
“…HDL concentration reduction is partially known to be related to aging ( 46 ); however, some centenarians presented with higher HDL-C levels ( 47 ), suggesting the association between high HDL levels, anti-atherosclerosis, and longevity. Policosanol supplementation reportedly elevated the HDL-C levels remarkably ( 48 ) and tendentially ( 49 ) in animal models and significantly in human studies ( 15 , 22 , 50 ). In this study, the effect of policosanol in increasing the HDL-C levels concurs with the above reports ( Figure 1B ).…”
Section: Discussionmentioning
confidence: 96%